One-year survival among patients with ST-elevation myocardial infarction in Peru - Chacón-Diaz, Manuel (2022)
Objectives. To determine one-year survival and factors associated with mortality in patients with STsegment elevation myocardial infarction in Peru. Methods. An analysis was made of the cohort of patients included in the PERSTEMI-II registry during the year 2020, in whom survival at one year after the event and its risk factors were evaluated using Kaplan-Meier survival analysis and Cox regression. Results. Of 374 patients in the PERSTEMI-II study, 366 (97.9%) completed follow-up up to one year after the event with a survival rate of 85%. Successful reperfusion was related to better survival at 1 year (hazard ratio [HR]=0.30, 95% CI: 0.14-0.62, p=0.001). Age (HR=1.04, 95% CI: 1.01-1.07, p=0.003), chronic kidney disease (HR=2.15, 95% CI: 1.04-4.39, p=0.037) and cardiogenic shock (HR=6.67, 95% CI: 3.72-11.97, p<0.001) were factors of higher mortality at 1-year follow-up. Conclusion. The PERSTEMIII registry is the first Peruvian registry that provides data on survival after ST-segment elevation myocardial infarction, which is 85% at one year. Successful reperfusion improves survival at one-year post infarction.